Changes in Objectively Measured Physical Activity (Performance) After Epidural Steroid Injection for Lumbar Spinal Stenosis - Tomkins-Lane, Christy C.; Conway, Justin; Hepler, Charles; Haig, Andrew J. (Archives of physical medicine and rehabilitation, 2012)
Tomkins-Lane CC, Conway J, Hepler C, Haig AJ. Changes in objectively measured physical activity (performance) after epidural steroid injection for lumbar spinal stenosis. To examine changes in objectively measured physical activity (performance) at 1 week following epidural steroid injection for lumbar spinal stenosis. Prospective cohort. University spine program. Individuals (N=17) who were undergoing fluoroscopically guided epidural steroid injection for symptomatic lumbar spinal stenosis (mean age ± SD, 70.1±6.7; 47% women). Fluoroscopically guided epidural injection. The 2 primary outcomes, measured with accelerometers, were total activity (performance) measured over 7 days and maximum continuous activity (capacity). Walking capacity was also assessed with the Self-Paced Walking Test, and subjects completed the Oswestry Disability Index, Swiss Spinal Stenosis Questionnaire, Medical Outcomes Study 36-Item Short-Form Health Survey, visual analog pain scales, and body diagrams. At 1 week postinjection, 58.8% of the subjects demonstrated increased total activity and 53% had increased maximum continuous activity, although neither change was statistically significant. Significant improvements were observed in a number of the self-report instruments, including the Physical Function Scale of the Swiss Spinal Stenosis Questionnaire, general health (Medical Outcomes Study 36-Item Short-Form Health Survey), role-limitation emotional (Medical Outcomes Study 36-Item Short-Form Health Survey), leg pain intensity (visual analog pain scales), and presence of leg weakness. While patients perceived improvements in pain and function following injection, these improvements were not reflected in significant changes in performance or capacity. Future studies will continue to find value in subjective measures of pain and quality of life. However, with modern technology, performance is no longer a subjective variable. Use of activity monitors to objectively measure performance can result in more rigorous validation of treatment effects, while simultaneously highlighting the potential need for additional postinjection rehabilitation aimed at improving performance.